Immune response to influenza vaccination in children with cancer. Issue 9 (2nd September 2018) - Doganis, Dimitrios; Kafasi, Athanasia; Dana, Helen; Spanakis, Nikolaos; Baka, Margarita; Pourtsidis, Apostolos; Sdogou, Triantafyllia; Vintila, Artemis; Rafailidou, Vaia; Chantzi, Panagiota; Servitzoglou, Marina; Bouhoutsou, Despina; et al.
ABSTRACT: The aim of this study was to evaluate the ability of influenza immunization to evoke a protective immune response among children with cancer. We evaluated 75 children with cancer who received influenza vaccination. Hemagglutination Inhibition Antibody titers were determined before and after vaccination. The protective rates after vaccination were 79% for H1N1, 75% for H3N2 and 59% for influenza B virus whereas the seroconversion rates were 54%, 44% and 43% respectively. The differences pre- and post-vaccination were significant regardless the method which was used: seroprotection changes, seroconversion and geometric mean titers analyses. Variables such as the pre-vaccination antibody titers, the time when the responses were measured after the vaccination, the age and the type of malignancy as well as the absolute lymphocyte count were found to be correlated with the immune response but the findings were different for each vaccine subunit. In conclusion, influenza vaccination provides protection in a remarkable proportion of pediatric cancer patients whereas this protection is more obvious against H1N1 and H3N2 compared to influenza B. The immune response after vaccination is significant and seems to be influenced by a variety of factors.